Chemical defense mechanisms of soybean genotypes against lepidopterans - Costa, Josicleia Oliveira; Peña Arroyo, Victoria P.; Núñez-de la Rosa, Yeison; Ballesteros-Ballesteros, Vladimir A.; Nisperuza Toledo, Jorge Luis; Birolli, Willian Garcia (Frontiers in Plant Science, 2026)
Soybean (Glycine max [L.] Merrill) is one of the world’s most important agricultural crops, playing a strategic role in global protein and lipid production. However, its productivity is severely constrained by defoliating lepidopterans such as Anticarsia gemmatalis, Chrysodeixis includens, Helicoverpa armigera, and species of the genus Spodoptera, which cause substantial yield losses due to their intense herbivory and remarkable adaptive capacity. Conventional management strategies relying on chemical insecticides provide only partial control and are associated with negative environmental and ecological impacts. Although transgenic Bt soybeans have demonstrated efficacy against certain pest species, they exhibit limited toxicity toward Spodoptera spp. In this context, the exploitation of soybean genotypes with natural resistance represents a promising alternative within the framework of Integrated Pest Management. This review summarizes the principal chemical defense mechanisms underlying soybean resistance to lepidopterans, emphasizing the role of secondary metabolites, such as flavonoids, phenolics, tannins, and volatile organic compounds, that function as toxic, antinutritional, or repellent agents. Several genotypes, including IAC 100, PI 227687, and PI 227682, have displayed resistance to multiple caterpillar species, establishing themselves as valuable genetic resources for breeding programs. Furthermore, recent studies indicate that environmental conditions, plant developmental stage, and multitrophic interactions strongly modulate the expression of these defense traits. A comprehensive understanding of the chemical interactions within the soybean-lepidopteran system is therefore crucial for the development of more tolerant and sustainable cultivars, reducing dependency on insecticides and slowing the evolution of insect resistance. Future perspectives emphasize the integration of omics technologies, bioinformatics, and biotechnology to elucidate key metabolic pathways and accelerate the generation of resistant soybean varieties, ultimately promoting higher productivity and agricultural sustainability.